Experimental and numerical investigation of combined sensible–latent heat for thermal energy storage at 575 °C and above. (April 2015) - Zanganeh, G.; Khanna, R.; Walser, C.; Pedretti, A.; Haselbacher, A.; Steinfeld, A.
Highlights: A packed bed of phase change material (PCM) and rocks is used for heat storage. Air is used as the heat-transfer fluid. The concept stabilizes the outflow temperature for approximately 90 min. The stabilization is achieved with less than 5 vol.% of PCM. Abstract: The design, testing, and modelling of a high-temperature thermocline-type thermal energy storage (TES) are presented. The TES concept uses air as the heat-transfer fluid and combines sensible and latent heat for stabilizing the discharging outflow air temperature. A 42 kWhth lab-scale prototype of 40 cm diameter was fabricated, containing a 9 cm high layer of encapsulated phase change material (AlSi12 ) on top of a 127 cm high packed bed of sedimentary rocks with a mean diameter of about 3 cm. A two-phase transient heat transfer model of the thermal storage cycle was numerically formulated and experimentally validated with measured thermoclines during charging and discharging obtained with the lab-scale prototype. The thermal inertia of the experimental setup and the radial variation of void fraction due to the small tank-to-particle diameter ratio affected the validation process. The outflow air temperature during discharging was stabilized around the melting temperature of AlSi12 of 575 °C. The thermal losses stayed below 3.5% of the input energy for all the experimental runs.